The moving targets of expanded newborn screening for inborn errors of metabolism: the experience in Portugal - Marcão, Ana (2020)
The Portuguese programme for newborn screening (NBS) includes 26 diseases (Congenital Hypothyroidism, 24 metabolic disorders and Cystic Fibrosis), presenting an estimated overall incidence of 1: 1.100 affected newborns (NB). It was established in the late 70s, starting with phenylketonuria (PKU), and soon after, congenital hypothyroidism (CH) screening. Since 2004, the screening for inborn errors of metabolism (IEM) started to be done through tandem mass spectrometry (MS/MS) which allowed extension to 24 metabolic diseases. The global frequency of all IEM integrated into the programme is estimated to be 1: 2.253. As expected, an increase in the detection rate of IEM was observed after extended-NBS implementation. MCAD deficiency revealed to be the most frequent metabolic disorder screened by MS/MS in Portugal, with a frequency even higher than PKU (1: 7.499 and 1: 10.772, respectively). The detection of other diseases like carnitine uptake deficiency (CUD), very long chain acyl CoA dehydrogenase deficiency (VLCADD), carnitine palmitoyl translocase type I deficiency (CPTID) or carnitine palmitoyltranslocase type II deficiency (CPTIID), also started to be a reality. While for most of these diseases newborn screening revealed tremendously beneficial for newborns and families, in other cases like methylcrotonyl CoA carboxylase deficiency (MCCD) and methionineadenosyltransferase (MAT I/III) deficiency, the benefits are not equally evident and raise some questions about their inclusion in the panel of screened disorders, which since 2019 also includes Cystic Fibrosis. Enlarging the number of screened diseases, some of them demanding urgent clinical intervention in the first days of life, allowed the increase in the number of NBS-detected cases, but also brought additional challenges. Some subjects like the collection time frame, the time that it takes to arrive into the laboratory and the laboratory turnaround time became critical, and required special attention. Additional issues like specificity and sensitivity have also been carefully assessed along these years, and measures as the recent implementation of additional second tier tests for IEM screening allowed an important improvement in NBS-performance. Quality management is equally important and efforts have been made for ISO 15189 accreditation, which was already achieved for CH screening. Always attentive to new scientific and medical advances and to international recommendations, the Portuguese programme always tries to keep as an updated and dynamic program.